Nectar ecology of the endemic epiphytic hummingbird-pollinated bromeliad Vriesea altodaserrae: secretion dynamics and pollinator visitation pattern - Nunes,Carlos E. P. (2018)
ABSTRACT Hummingbirds are the main pollinators of most bromeliad species, whose nectar traits usually respond to the selective pressures imposed by pollinators. Considering the specialization of hummingbird-pollinated bromeliads, we expect a close relationship between nectar ecophysiology and the needs of the main pollinators. In this sense, we studied the nectar ecology of the endemic epiphytic bromeliad Vriesea altodaserrae by assessing its nectar traits to address the following questions: i) do flowers respond to successive experimental removals of nectar? ii) is hummingbird visitation frequency related to nectar secretion pattern? We found that V. altodaserrae depended completely on hummingbirds for sexual reproduction, and nectar composition was consistent with that of most hummingbird-pollinated species. Most of the nectar was secreted at bud stage and, if not removed, flowers reabsorb it at the end of their lifespan. Total nectar production did not change after successive removals, and nectar secretion rhythm did not affect the frequency of hummingbird visits. Vriesea altodaserrae was visited by two-thirds of the hummingbird species recorded at the study site, but especially by those of Trochilinae subfamily, suggesting specialization for this group of hummingbirds and highlighting the importance this endemic bromeliad as a keystone species in areas of highland Atlantic forest.